DEVELOPMENT OF THE TOURIST SERVICES MARKET IN UKRAINE UNDER CONDITIONS OF TRANSFORMATION CHANGES - Підгірна, Валентина Никифорівна; Філіпчук, Наталія (GeoJournal of Tourism and Geosites, 2020)
The article is dedicated to the investigation of market functioning peculiarities of tourist services in Ukraine and the influence of the level of profits of the population on the development of the tourist branch. A characteristic of theoretical bases of the category «tourist service» is investigated from different approaches. Basic tendencies of the market development of tourist services for the period 2014-2018 were analysed. Diagnostics of tourist flows according to the regions of the world was performed and the tendency of tourism role growth both on the local as well as on the international levels was established. Due to the usage of the systemic analysis method a close connection was proved to be between the level of profits of a consumer and the level of profits of a tourist enterprise which influences on the formation of gross domestic product of the country.
DEVELOPMENT OF THE TOURIST SERVICES MARKET IN UKRAINE UNDER CONDITIONS OF TRANSFORMATION CHANGES
Keywords: туристична індустрія; туризм; туристичні потоки; туристичний оператор; туристичний ринок; менеджмент туристичної індустрії; туристична інфраструктура; Регіональний туризм